(untitled) (Research, Society and Development, 2022)
The use of medicinal plants is a very old practice. According to the World Health Organization, approximately 80% of the population uses plants for therapeutic purposes. Medicinal plants are plant species with several active principles, which can act in the human and animal body to fight many diseases. Despite its beneficial health effects, many studies report contamination by heavy metals, both from natural and anthropogenic sources. In many countries, medicinal plants are used and marketed with little or no supervision for the presence of heavy metals. The objective of this article was to qualitatively analyze publications, carried out in the last 10 years, on contamination by heavy metals in medicinal plants, in order to understand the mechanisms of tolerance of plants to the presence of heavy metals, to know the legislation that guides the use of medicinal plants and understand what still needs to be done to avoid contamination by heavy metals through medicinal plants. For the elaboration of this review, a search was carried out in the Scopus database, using the terms “heavy metal” and “medicinal plants”. After the search, the works were analyzed using the VOsviewer® software. It is concluded that the interest in plants in the last 10 years is constant. Plants have different ways to tolerate the presence of heavy metals. New regulations need to be implemented, the inspection of herbal products needs to be more rigorous and the population needs to be better informed about the therapeutic properties based on scientific work and about the possible contamination present in plants.